2006
DOI: 10.1016/s0968-8080(06)27231-8
|View full text |Cite
|
Sign up to set email alerts
|

Blood Blockages and Scolding Nurses: Barriers to Adolescent Contraceptive Use in South Africa

Abstract: A third of adolescent girls in South Africa become pregnant before the age of 20, despite contraception being free and mostly accessible. This qualitative study was undertaken in Limpopo Province in 1997 on the barriers to adolescent girls accessing clinic services for contraception. Thirty-five in-depth interviews and five group discussions were conducted with girls aged 14-20, and interviews with nursing staff at 14 clinics. Many of the girls described pressure from male partners and family members to have a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

24
300
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 249 publications
(328 citation statements)
references
References 21 publications
24
300
4
Order By: Relevance
“…By overcoming some logistical and stigma-related barriers to use of contraception [11][12][13], data from the m4RH pilot demonstrate the potential to increase contraceptive knowledge and behavior change among young people in Kenya. The m4RH program delivers contraception messages in a format that is concise and consistent with clinicbased counseling messages.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By overcoming some logistical and stigma-related barriers to use of contraception [11][12][13], data from the m4RH pilot demonstrate the potential to increase contraceptive knowledge and behavior change among young people in Kenya. The m4RH program delivers contraception messages in a format that is concise and consistent with clinicbased counseling messages.…”
Section: Discussionmentioning
confidence: 99%
“…Barriers to youth accessing clinics for contraception include limited or misinformation; cost and convenience of clinic services; privacy concerns; and provider biases toward sexual activity among young unmarried individuals [11][12][13]. Mobile phones may address some of these barriers; while there is 1 doctor for every 10 000 Kenyans [14], there are approximately 6200 mobile phone subscriptions per 10 000 people [8].…”
Section: Introductionmentioning
confidence: 99%
“…If the majority of the pregnancies among teenagers are unwanted, this raises the question about why young people are not protecting themselves. Findings from three reviews of studies conducted in sub-Saharan Africa (Macleod 1999a(Macleod ,1999bMacleod and Tracey 2010) indicate that young women's use of contraceptive methods is limited by several factors including violent and coercive sexual relationships, lack of knowledge, limited access to contraceptive methods, lack of control over contraception decisions, and concerns over the perceived side effects of family planning methods (Macleod and Tracey 2010;Wood and Jewkes 2006). In the particular case of condom use, ever received sex education in school, ever attended school, exposure to the radio, condom use self-efficacy, perceived social norms, attitude towards condom use, positive behavioural control beliefs and positive outlook on life have all been reported to predict the intention to use condoms among young people in different African settings (Boer and Tshilidzi Mashamba 2007;Macleod and Tracey 2010;Rijsdijk et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…However, research in South Africa to date has not identified factors associated with women's increased risk of having an AEP. In South Africa, social norms favouring fertility and childbearing (Wood & Jewkes, 2006); barriers to attendance of and access to family planning clinics (Stephenson, Baschieri, Clements, Hennink, & Madise, 2007); and a lack of accurate and complete information about how to use contraceptives effectively (Beksinska, Rees, Nkonyane, & McIntyre, 1998) are among factors that prevent contraceptive use.…”
mentioning
confidence: 99%